2014
DOI: 10.1590/0100-2945-269/13
|View full text |Cite
|
Sign up to set email alerts
|

Germinação de sementes de romäzeiras (Punica granatum L.) de acordo com a concentração de giberelina

Abstract: resumo -a romãzeira (Punica granatum l.) é fruteira de porte arbustivo, utilizada geralmente como planta ornamental e explorada quanto a suas características medicinais. Seus frutos apresentam cavidades internas onde estão alojadas numerosas sementes e sem a presença de endosperma. estas sementes apresentam certa dificuldade para germinar, sendo que se conseguiu atingir porcentagens satisfatórias de germinação com a utilização de estratificação, que é processo necessário para a quebra da dormência fisiológica,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
0
9
1
3
Order By: Relevance
“…Due to the fact that no difference among GA 3 doses (0; 100; 200; 300; 400 mg L -1 ) was observed for seed germination, Takata et al (2014) suggested that the hormonal balance of pomegranate seeds inluences germination (which may explain why the GA 3 did not inluence the germination process) and observed a high percentage for all treatments. However, the authors emphasize that the seeds were obtained from a commercial orchard, suggesting the genetic characteristic must have inluenced their results.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Due to the fact that no difference among GA 3 doses (0; 100; 200; 300; 400 mg L -1 ) was observed for seed germination, Takata et al (2014) suggested that the hormonal balance of pomegranate seeds inluences germination (which may explain why the GA 3 did not inluence the germination process) and observed a high percentage for all treatments. However, the authors emphasize that the seeds were obtained from a commercial orchard, suggesting the genetic characteristic must have inluenced their results.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Rawat et al (2010) obtained a substantial response with higher, faster, and uniform germination, as well as signiicant growth at the early seedlings stage, when using 25 and 30 days of cold stratification (5 o C) on pomegranate seeds. Despite this, Takata et al (2014) did not observe a positive germination response for a gibberelic acid (GA 3 ) treatment on pomegranate seeds from a commercial orchard.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Partes desse vegetal são utilizadas pela população de forma direta (através de infusões com a casca do fruto) ou em produtos naturais comercializados pelo país. Com isso, tem despertado o interesse de pesquisadores em investigar tais e outras possíveis características e ratificar o seu uso (DEGASPARI et al, 2011;TAKATA et al, 2014;TRINDADE et al, 2009).…”
Section: Introductionunclassified